Quantitative vibration perception threshold in assessing diabetic neuropathy: Is the cut-off value lower for Indian Subjects? [Q-VADIS Study] - Ghosal, Samit; Stephens, Jeff; Mukherjee, Aninda (Diabetes & metabolic syndrome clinical research & reviews, 2012)
The aim was to compute a normative data of VPT [Vibration Perception Threshold], compare results of VPT among type 2 diabetes patients with and without neuropathy, validate VPT taking NDS [Neuropathy Disability Scores] as gold standard and suggest a cut off value for the Indian population. A clinic based case-control study was conducted at Nightingale Hospital (NH) in Kolkata for 2 months duration. Fifty type 2 diabetes patients (who were detected with by fasting plasma glucose or on medication) reporting at OPD (Out Patent Department) were randomly selected and informed consent was obtained. The age range was 20–65 years and other common causes of neuropathy were excluded. Same number of control patients without diabetes and reporting at the same hospital during the study period in the similar age range were selected. The normative data of VPT for mean of 4 sites (malleoli and great toe) was 11.3±4.9mV. The VPT value was significantly higher among diabetic patients with neuropathy compared to non-neuropathic and non-diabetic patients. Considering NDS score as gold standard lowering the cutoff value of VPT from 25mV to 20mV increased the sensitivity from 50% to 62.5% in detecting diabetic neuropathy compared to NDS taken as a gold standard. It was found that lowering the cut off value of VPT in Indian population increased the sensitivity of the test to detect diabetic neuropathy without hampering the specificity. There is however no indication that a lower cut off VPT value is justified as of now.